PENINGKATAN HASIL BELAJAR SISWA MELALUI METODE PRAKTIKUM BERBASIS LINGKUNGAN PADA MATERI LAJU REAKSI DI SMAN 1 KARANGNUNGGAL - Rohayah, Dede (LPPM Universitas Bina Bangsa, 2023)
Optimal learning outcomes are supported by the teacher's ability to teach and use facilities to support student learning outcomes. In fact, learning at SMAN 1 Karangnunggal still uses old methods which do not improve learning outcomes. Students tend to observe and memorize material and the teacher's lack of ability to use existing facilities such as laboratories and the limited materials needed for practicum. The purpose of this study was to determine teacher activity, student activity, improve learning outcomes and student responses through an environment-based practicum method on reaction rate material. This research is a classroom action research. Data was collected through 3 cycles using observation, questionnaires and tests. Then the resulting data is analyzed through the data reduction stage, the data presentation stage and the conclusion drawing stage. The research results obtained an increase in teacher activity and student activity marked by the percentage (88%) and (80%), the average acquisition achieved from learning outcomes in cycle I was 68.50, Cycle II was 73.16 and in cycle III was 77, 83. This shows that there is an increase in learning outcomes after following the learning process. And it can be concluded that this environment-based practicum method is able to improve student learning outcomes